2011
DOI: 10.1111/j.1748-1716.2011.02359.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of breast cancer cell migration via up‐regulation of TASK‐3 two‐pore domain K+ channel

Abstract: These results show that an increase in TASK-3 expression levels, which could be modulated by PKC activation, reduces cell migration/invasion in breast cancer cells and suggest that modulation of TASK-3 expression may regulate metastasis of breast cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 23 publications
3
27
1
1
Order By: Relevance
“…In the present study, LRRC3B expression levels decreased in breast cancer MDA-MB-231 and MCF-7 cells that were treated with different concentrations of bupivacaine, indicating that the administration of bupivacaine to breast cancer tumor cells suppressed the expression of LRRC3B. A number of studies have revealed that bupivacaine administration during cancer surgery serves a crucial role in cancer recurrence and metastasis by promoting cell migration (27,28). In line with previous studies, the data of the present study showed that 50 µg/ml bupivacaine yielded the maximum increase breast cell invasion.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, LRRC3B expression levels decreased in breast cancer MDA-MB-231 and MCF-7 cells that were treated with different concentrations of bupivacaine, indicating that the administration of bupivacaine to breast cancer tumor cells suppressed the expression of LRRC3B. A number of studies have revealed that bupivacaine administration during cancer surgery serves a crucial role in cancer recurrence and metastasis by promoting cell migration (27,28). In line with previous studies, the data of the present study showed that 50 µg/ml bupivacaine yielded the maximum increase breast cell invasion.…”
Section: Discussionmentioning
confidence: 94%
“…Incidence of PDAC correlates with increasing age and therefore is an increasing problem as world population is aging [16]. Dysfunction of ion channels is an emerging field in cancer research and differential expression of multiple classes of ion channels has been reported for different cancer tissues [2022, 28, 29, 31, 35, 43]. Plasma membrane ion channels are involved in apoptosis [19], differentiation, and proliferation [17, 28], and are further associated with cell migration [15, 38] and cell volume regulation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Within the K V family, K V 11.1 (hERG) shows altered expression in an array of cancer types and has been shown to impact cellular proliferation (melanoma, colorectal cancer and Barrett's esophagus), migration (melanoma, thyroid and breast cancer), malignant transformation (head & neck carcinoma) and apoptosis (gastric cancer). While K V 11.1 is most frequently reported for its role in cancer, an array of other K + channels have also been proposed as molecular components promoting cancer development and progression [9], [10], [24][80] (summarised in Table 1). …”
Section: Introductionmentioning
confidence: 99%